Electrochemical "read–write" microscale patterning of boron doped diamond electrodes. Issue 1 (12th November 2014) - Patten, Hollie V.; Hutton, Laura A.; Webb, Jennifer R.; Newton, Mark E.; Unwin, Patrick R.; Macpherson, Julie V.
Abstract : We report the use of scanning electrochemical cell microscopy (SECCM) for the electrochemical "read–write" patterning of boron doped diamond electrodes. Abstract : Scanning electrochemical cell microscopy is utilised as a read–write pipette-based probe to both electrochemically modify the local surface chemistry of boron doped diamond and "read" the resulting modification, at the micron scale. In this specific application, localised electrochemical oxidation results in conversion of the H-terminated surface to –O, electrochemically visualised by monitoring the current change for reduction of Ru(NH3 )6 3+ . This methodology, in general, provides a platform for read–write analysis of electrodes, opening up new analytical avenues, particularly as the pipette can be viewed as a microfluidic device.